A cross-cultural study of the elementary forms of religious life: shamanistic healers, priests, and witches - Winkelman, Michael J. (Religion, brain & behavior, 2021)
Empirical cross-cultural research provides a typology of magico-religious practitioners and identifies their relations to social complexity, their selection-function relationships, and reveals their biosocial bases. Different practitioner types and configurations are associated with specific ecological and political dynamics that indicate a cultural evolutionary development. Relations between practitioners’ selection processes and professional activities reveal three fundamental structures of religions: (1) selection and training involving alterations of consciousness used for healing, manifested in Shamans and other shamanistic healers; (2) social inheritance of leadership roles providing a hierarchical political organization of agricultural societies, manifested in Priests; and (3) attribution of a role involving inherently evil activities, and manifested in the Sorcerer/Witch. Shamans were transformed with foraging loss, agricultural intensification, warfare, and political integration into Healers and Mediums. Priests are predicted by agriculture and political integration beyond the local community, representing the emergence of a new stratum of magico-religious practice. Priests are also responsible for political and social conditions that significantly predict the presence of the Sorcerer/Witch. These findings suggest three distinctive biosocial structures of magico-religious activity related to alterations of consciousness and endogenous healing processes; hierarchically integrated social organization; and social persecution and incorporation.